Life of the cell: Is it important how cells die? - Kravic-Stevovic, Prof. Tamara; Martinović, Tamara; Ćirić, Darko; Rakočević, Jelena; Paunković, Ivana; Zaletel, Ivan; Despotović, Sanja; Ćetković-Milisavljević, Mila; Bumbaširević, Vladimir (Medical Research, 2025)
Cell death emerges during embryonic development, and is preserved after the birth as an important process for maintaining homeostasis by removing damaged or aged cells. Two forms of cell deaths exist: accidental and regulated cell death. Necrosis is an accidental, unregulated, passive form of cell death that occurs due to the collapse of cellular homeostatic mechanisms under extreme non-physiological conditions. Regulated cell death is an active, energy-dependent process that functions as a physiological mechanism for maintaining homeostasis and in numerous pathological conditions when it provides selective elimination of potentially dangerous or infected cells. There are many types of regulated cell death: intrinsic and extrinsic types of apoptosis, autophagy dependent cell death, necroptosis, pyroptosis, ferroptosis, parthanatos, mitochondrial permeability transition-driven necrosis, lysosome-dependent cell death, immunogenic cell death, entosis and NET-osis. Different types of cell death are interconnected. Abnormal activation of the different forms of cell death can cause diseases. Dysregulation of the apoptotic program can lead to hyperplasia, autoimmune diseases and tumorigenesis, pyroptosis is associated with bacterial infection and necroptosis with human inflammatory skin diseases and carcinogenesis. Understanding the regulatory mechanisms of apoptosis led to discovery of BH3 mimetics, drugs used for treatment of some types of B cell malignancies. Drugs that target necroptosis, pyroptosis and autophagy are under investigation and could be potentially used in the future as therapies for various diseases, including cancer. The aim of this review is to summarize new knowledge about the processes of cell death, and to emphasize the importance of newly discovered molecular pathways regulating various types of cell death, enhancing our comprehension of health and disease.
Keywords: cell death, necrosis, apoptosis, autophagy